(untitled) (ENTHYMEMA, 2016)
Presentiamo la cronaca del seminario scientifico-didattico internazionale Gumanitarnaja škola v Rossii i perelom 1917 g.: èkzistenciajl’noe izmerenie / Humanities in Russia and the Break of 1917: the Existential Dimension, svolto nella filiale di Perm’ dell’Università di ricerca internazionale «Higher School of Economics» dal 25 al 28 agosto 2015. We present the chronicle of the international scientific-didactic seminar Gumanitarnaya shkola v Rossii i perelom 1917 g .: ekzistentsiajlnoe izmerenie / Humanities in Russia and the Break of 1917: the Existential Dimension, held in Perm filial of Narional Research University "Higher School of Economics» (25-28 August 2015).